The Effect of Yoga Education on Balance and Quality of Life in Postmenopausal Osteoporosis - Şansın Tüzün; İlknur Aktaş; Ülkü Akarırmak; Sevtap Sipahi; Fikret Tüzün (Galenos Yayinevi, 2004)
Osteoporotic vertebra and hip fractures are major cause of dysfunction, disability, mortality and loss of life quality in our growing and ageing population. In the premenopausal period exercises prevent rapid bone loss due to estrogen deficiency and increase muscle strength, mobility and flexibility thereby decreasing risk of falls and fractures. Yoga exercises, which have been an inseperable part of the Eastern culture for hundreds of years, are now being used in the field of osteoporosis rehabilitation.Yoga has a positive effect on balance, posture, flexibility, and life quality by its effects on balance, stretching, relaxation and strengthening. The aim of this study was to evaluate the effect of yoga exercises in postmenopausal osteoporotic women on balance and life quality and to compare the result with a classic osteoporosis exercise program. Twenty-six postmenopausal osteoporotic women over 55 years of age were included in the study. A neuromusculer test battery and the QUALEFFO as life quality index were used for assessment of balance and life quality. The results showed that yoga education has a positive effect on pain, physical functions, social functions, general health perception and balance. As a conclucion yoga appers to be an alternative modality for the rehabilitation of osteoporotic subjects.